Effect of acrylonitrile styrene acrylate on mechanical, thermal and three-body abrasion behaviors of eucalyptus fiber reinforced polyvinyl chloride composite. (24th February 2021) - Zhang, Keping; Hamza Bichi, Abdulmalik; Yang, Junqian
Abstract: The effect of different content (0–20 wt%) Acrylonitrile-styrene-acrylic (ASA) on mechanical, thermal and three-body wear behaviors of eucalyptus fiber/polyvinyl chloride (EF/PVC) composites were studied in this research. The results show that the mechanical properties of the composites such as impact strength, tensile strength, flexural strength and flexural modulus increased with increasing ASA content lower than 15 wt%. The addition of 15 wt% and 20 wt% ASA can improve thermal stability of the EF/PVC composites in the early period of the heating, and the effect weakened on later stage due to the thermal degradation of ASA, which occurred in the temperature range 416°C–442°C. The three-body wear resistance of the EF/PVC composites can be improved by ASA, and the abrasive wear mechanism of the composites was predominated by linear travel, sand particle plough and cut action, ASA and PVC plastic deformation, and fibers debonding.